Analysis of Initiation and Growth of Plasma Channels Within Non-Mixed Dielectric Liquids - Khalaf, Thamir H. (Iraqi Journal of Physics, 2010)
Pre-breakdown phenomenon was investigated within the two, non-mixed dielectric liquids; transformation oil and cresol. Finite element technique was used to follow the initiation and growth of plasma channels (streamer discharge) within pin-plane configuration. That was done for different spacing between the pin-electrode and the liquid-liquid interface. Streamer growth model assumed that, the streamer initiation occurs at the region of the highest value of electric field. Our study shows that the streamer initiates at the tip of the pin and growths toward the other electrode. The study shows, too, that the streamer path controlled by the difference of permittivity of the two liquids and spacing distance of the liquid-liquid interface from the tip of the pin electrode. This type of studies is very important to give a good approximation for the high voltage equipments designing